Psychoemotional States and the Presence of Bruxism in Peruvian Dental Students - Estrada Murillo DDS, Nilvert A. (2018)
The aim of the study was to evaluate the relationship between psycho-emotional states and the presence of bruxism in a sample of students at a public School of Dentistry in Lima-Peru. The sample was 181 randomly selected students. Bruxism and the psycho-emotional states such as: stress, anxiety (state and trait) and depression were studied and measured through validated instruments. The results showed a low but highly significant correlation (p <0.001) between bruxism, stress, depression and the anxiety state. It is concluded that emotional states contribute to the presence of bruxism in dental students.